AN APPRAISAL OF THE EFFECTIVENESS AND EFFICIENCY OF NIGERIA'S COUNTER-TERRORISM APPROACH IN THE NORTH EAST - 2009-2021 - Roberts Anya Nkata (International Studies Journal, 2023)
This paper examined the effectiveness and efficiency of the Nigeria counter-terrorism approach in the North Eastern region of Nigeria from 2009 – 2021. The Nigeria counter-terrorism strategies have not effectively eradicated the Boko Haram sect; they have strategically continued the wanton destruction of lives and properties, resulting in an unprecedented threat to Nigeria's national security. Nigerian counter-terrorism strategies have depended heavily on the kinetic approach. The discussion applied Sir Gerald Templer's Heart and Mind counter-insurgency theory. The paper employed a quantitative approach to data collection and analysis. The paper, therefore, discovered that the Nigeria counter-terrorism strategies in the northeast have been ineffective and inefficient, as evidenced by the responses of 32% of respondents. The paper concludes that reliance on the kinetic approach, disconnection between policy and implementation, poor utilization of modern technology, poor inter-agency collaboration, and lack of morality and motivation are the major factors that have impinged the effectiveness and efficiency of Nigeria counter-terrorism approach in the North-East. The paper recommends winning the heart and minds of the general population and a less kinetic approach in addition to providing modern equipment, inter-agency collaboration, and feedback on policy implementation as the panacea for Boko Haram terrorism.